1990
DOI: 10.1017/s0022215100112563
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis: anatomical and clinical correlates

Abstract: One hundred and seven consecutive patients with acute and chronic epistaxis were examined to identify the site and nature of the source. Aetiological factors in the history, nasal anatomy or pathology were noted, along with the blood pressure and laboratory results.In most presentations an anterior bleeding point was isolated. Cautery usually sufficed in both anterior and posterior sources. No source was hidden behind a septal spur or deflection. Hypertension was associated with bleeding from the middle meatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 5 publications
1
38
1
3
Order By: Relevance
“…1,5 The incidence of neoplasm in this study is this study is 6% when compared to 2% reported by Nigel Padgham. 15 No vascular mass like nasopharyngeal angiofibroma was reported in this study. Thaha 14 in his study reported 8.3% abnormal coagulation profile.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…1,5 The incidence of neoplasm in this study is this study is 6% when compared to 2% reported by Nigel Padgham. 15 No vascular mass like nasopharyngeal angiofibroma was reported in this study. Thaha 14 in his study reported 8.3% abnormal coagulation profile.…”
Section: Discussionmentioning
confidence: 57%
“…This male predominance is similar to that reported by Safaya. 12 Study by Nighel Padgham, 15 Monux 2 et al also shows a male predominance. Age wise distribution in the study shows peak incidence between 51-60 years [28%].…”
Section: Discussionmentioning
confidence: 96%
“…Padgham showed that medical treatment is the most effective treatment for children with nasal bleed. 14 In severe posterior epistaxis, Foley's catheter is a very good option for posterior nasal packing. From our observation, endoscopic coagulation of the sphenopalatine artery, is a simple and alternative method of controlling posterior epistaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The peak presentation is the sixth decade with male dominance [4]. Adult pattern primary epistaxis is associated with the regular use of nonsteroidal antiinflammatory drugs, chronic alcohol consumption and hypertension.…”
Section: Discussionmentioning
confidence: 99%